Evaluasi Kinerja Perbankan Indonesia Pasca Pandemi Covid-19 Menggunakan Metode Hellwig - Djaja Perdana; Stephanus Andi Adityaputra (Akademi Akuntansi YKPN Yogyakarta, 2023)
The increase in non-performing loans during the Covid-19 pandemic forced the government to establish a credit restructuring policy for banks in Indonesia. Through this policy, it is expected that banks in Indonesia will be able to reduce the credit risk that arises and improve their financial performance. This study aims to evaluate the effectiveness of credit restructuring policies on the financial performance of Indonesian banks by measuring the variability of performance scores between banks with a multi-criteria decision-making (MCDM) approach using the Hellwig method and a comparison test between periods using the Wilcoxon Signed Rank Test. This research sample consists of 43 banks listed on the Indonesia Stock Exchange during 2020-2022. Evaluation using the Hellwig method obtained the score and performance ranking of each bank which was grouped into 5 categories, from very low to very high. in 2022, BACA and BEKS have very low scores and rankings. While BBSI and ARTO have very high scores and rankings. The comparative test results prove that the financial performance of Indonesian banks in 2022 is higher than in 2020 and 2021. The restructuring policy is proven to be able to improve banks performance in Indonesia and the effectiveness of the policy has reached its highest achievement in 3rd year since it was implemented.